Planejamento tributário, erosão da base tributável e o Plano de Ação do BEPS: uma análise acerca dos impactos do Plano de Ação da OCDE ma legislação brasileira - Soufen, Raquel Arruda (2016)
This study aims to analyze the recommendations proposed by the Organization for Economic Cooperation and Development ("OECD") together with the G20, with regard to combating base erosion profit split ("BEPS"). The study will be developed under the Brazilian legislation, and will examine how these guidelines can be implemented in Brazil, and if they could not, whether such guidelines would impact in any way our rules. In addition, it will be demonstrated that, despite the OECD's recommendations have not binding on Brazil, the BEPS's resolutions end up influencing the decisions of Brazilian multinationals